Still Life/Nature Morte: Review of Carol Freeman, Paper Tiger: A Visual History of the Thylacine - Borrell, Sally (Humanimalia, 2011)
Carol Freeman. Paper Tiger: A Visual History of the Thylacine. Human-Animal Studies series. Leiden and Boston: Brill, 2010. xiv + 287pp. €90, $128 pb.